Representation of Malays and Malay culture in the fiction of Lloyd Fernando and Che Husna Azhari - Wan Nur Madiha binti Ramlan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
In terms of demographics, Malaysia possesses such diversity with the multiple ethnic groups that make up the population of the country. Malaysia is a country that promotes its national diversity, unity, and harmony, and recently, the government has been promoting similar values within the 1Malaysia concept, a formula that aims to “foster unity” among the peoples of the country. However, the relationship between the dominant Malays and other races has always been a sensitive and taboo subject, ever since the May 13 incident in 1969, a sensitivity that far transcends the superficial image of harmony in the country. The Malays, which make up roughly around 65% of the population, and their culture would be the subject of this qualitative study. This paper investigates the representation of the Malays and Malay culture in the body of Malaysian postcolonial literature in the English language. The research will not only look at how the other ethnic groups represent the Malays in literature, but this study also aims to investigate how the Malays look at themselves. To achieve this aim, this study will examine a number of short stories by Che Husna Azhari and Green is the Colour (1993) by Lloyd Fernando. Due to the different ethnic backgrounds of these two writers, one being Malay and the other a non- Malay, a certain balance and objectivity could be reached. The work of these writers would supply sufficient evidence on the shaping of identity and representation of the Malays. The premise of this study would centre upon representation, race and ethnicity, nation and nationalism and the subaltern It is hoped that this study would allow for a better understanding of how stereotyping and national identity are shaped in Malaysia, as well as observe the aspirations and attempts, successful or otherwise, for national integration as proposed by the 1Malaysia concept.